Benz-bisimidazole-bridged perylenes - Linearly expanded chromophores - Schönamsgruber, Jörg; Hirsch, Andreas (European Journal of Organic Chemistry, 2015)
The synthesis and characterization of a new type of very large perylene-based molecules 9 are reported. The extension of the conjugated extgreekp system was accomplished by the facile condensation of two bay-functionalized perylene moieties with 1,2,4,5-tetraaminobenzene. The resulting chromophore in 9 consists of 35 conjugated extgreekp-electron pairs and, therefore, is comparable to pentarylenes and hexarylenes containing 31 and 36 conjugated extgreekp-electron pairs, respectively. The unsubstituted imine N atoms of the benz-bisimidazole bridges in 9 can be readily and reversibly protonated to give the dications 9aH22+. The twofold protonation of 9 is accompanied by a bathochromic shift of the main absorption band and pronounced fluorescence quenching. The experimental results were corroborated by quantum mechanical calculations.
Keywords: Chromophores; Dyes; NIR dyes; Perylene; Rylene dyes; π Conjugation

Fused Perylene-Phthalocyanine macrocycles: A new family of NIR-Dyes with pronounced Basicity - Schönamsgruber, Jörg; Maid, Harald; Bauer, Walter; Hirsch, Andreas (Chemistry - A European Journal, 2014)
Keywords: macrocycles; New near infrared dyes; Perylene; Phthalocyanines; Rylene

Grafting perylenes to ZnO nanoparticles - Schönamsgruber, Jörg; Zeininger, Lukas; Hirsch, Andreas (Chemistry - A European Journal, 2014)
A new prototype of dendritic perylenes suitable for the chemical functionalization of inorganic nanoparticles was synthesized and characterized. The bay-functionalized perylene core of these molecular architectures was coupled to a catechol moiety, which serves as an anchor group for the functionalization of metal oxides, in particular ZnO. To increase the solubility of both the perylene and the targeted hybrid nanostructures, a Newkome-type dendron bearing nine positive charges was introduced. This charge was also employed to stabilize the nanoparticles and further protect them from Ostwald ripening through Coulombic repulsion. ZnO quantum dots with an average diameter of 5nm were synthesized and functionalized with the perylene derivative. Successful functionalization was clearly demonstrated by dynamic light scattering, zeta-potential measurements, thermogravimetric analysis/MS, and UV/Vis and fluorescence spectroscopy. The generated particle dispersions were stable against agglomeration for more than eight weeks. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Highly Integrated Organic–Inorganic Hybrid Architectures by Noncovalent Exfoliation of Graphite and Assembly with Zinc Oxide Nanoparticles - Marcia, Mario; Vinh, Chau; Dolle, Christian; Abellan Saez, Gonzalo; Schönamsgruber, Jörg; Schunk, Torsten; Butz, Benjamin; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2016)
Liquid-phase exfoliated few-layer graphene flakes are noncovalently functionalized with tailor-made cationic water-soluble perylene diimides. By using a straightforward dip-coating approach, homogeneous ultrathin films consisting of interpenetrated nanoarchitectures can be achieved by incorporation of anionic ZnO nanoparticles. These 0D/2D assemblies pave the way for the development of novel graphene-based composite materials.
Keywords: graphene; hybrid materials; layer-by-layer assembly; nanoparticles; supramolecular chemistry

Nickel oxide nanostructured electrodes towards perylenediimide-based dye-sensitized solar cells - Feihl, Sebastian; Costa Riquelme, Rubén Dario; Pflock, Stephan; Schmidt, Cordula; Schönamsgruber, Jörg; Backes, Susanne; Hirsch, Andreas; Guldi, Dirk Michael (RSC Advances, 2012)
In this work, we have realized nickel oxide (NiO) electrodes that serve as photocathodes in p-type dye-sensitized solar cells (p-DSSCs) sensitized by dendronized perylenediimides (PDIs). To this end, two different approaches in terms of preparing NiO nanoparticle pastes were pursued to fabricate mesoporous electrodes on conductive fluorine doped tin oxide (FTO) glass substrates. Firstly, commercially available NiO nanoparticles were dispersed in a mixture of ethanol and terpineol. Here, in order to obtain a mesoporous network two types of ethylcelluloses (EC), that is, EC 5-15 and 30-50 mPa s, were added in 1:1 weight ratios. Following the evaporation of ethanol, the resulting pastes were spread on FTOs by doctor blading and calcinated at different temperatures. Importantly, the calcination temperature evolved as a crucial aspect in developing efficient electrodes. Nevertheless, the visual appearance of these NiO electrodes prompts a fairly heterogeneous coverage. To circumvent the aforementioned problem, a second approach en route to homogenous electrodes was investigated. In that particular case, commercial NiO nanoparticles were mixed with a mixture of EC 5-15 and 30-50 mPa s at a 1:1 weight ratio, with triacetin as a plasticizer in ethanol. In doing so, pastes containing 7 wt% EC, 3 wt% triacetin, and 3 to 20 wt% NiO nanoparticles were prepared. Most importantly, scanning electron microscopy (SEM) images corroborated the fact that the resulting electrodes revealed a dense coverage on FTOs. In addition, further characterizations ranging from UV/Vis transmission spectroscopy and conductivity measurements to Barrett-Joyner-Halenda (BJH) pore size and volume analysis were carried out. In the final step, the applicability of the new NiO photoelectrodes for p-DSSCs was successfully demonstrated by utilizing two types of PDIs, namely a symmetric 1 and a non-symmetric dendronized 2. Key aspects such as time dependence of dye uptake, hole lifetime and resistance features of the electrodes under operation conditions were investigated. © 2012 The Royal Society of Chemistry.

Synthesis and aggregation properties of polycationic perylenetetracarboxylic acid diimides - Schönamsgruber, Jörg; Schade, Boris; Kirschbaum, Rolf; Li, Jing; Bauer, Walter; Boettcher, Christoph; Drewello, Thomas; Hirsch, Andreas (European Journal of Organic Chemistry, 2012)
The synthesis and structural characterization of a first family of dendronized polycationic perylenetetracarboxylic acid diimides (PDIs) 7, 8, and 10 is reported. They were obtained by amide coupling reactions of pyridinium salt head groups with terminal carboxylic groups of Newkome-dendron-type functionalized PDIs. Resulting pyridinium-terminated PDIs 7, 8, and 10 are highly water-soluble, independent of the pH value. This is due to 6, 18, and 9 permanent positive charges, respectively. PDIs 7 containing the smaller first-generation dendrons exhibit a pronounced aggregation behavior in water. This was studied by absorption and fluorescence spectroscopy, by pulsed-gradient spin-echo (PGSE, DOSY) NMR measurements, and by cryo-transmission electron microscopy (cryo-TEM). The counterparts containing the bulkier second-generation dendrons hamper aggregation, and as a consequence intermolecular π-π stacking interactions between the perylene cores is suppressed. © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Two-dimensional delocalized states in organometallic bis-acetylide networks on Ag(111) - Yang, Zechao; Gebhardt, Julian; Schaub, Tobias; Sander, Tim; Schönamsgruber, Jörg; Soni, Himadriben; Görling, Andreas; Kivala, Milan; Maier, Sabine (Nanoscale, 2018)

Very Facile Polarity Umpolung and Noncovalent Functionalization of Inorganic Nanoparticles: A Tool Kit for Supramolecular Materials Chemistry - Zeininger, Lukas; Petzi, Stefanie; Schönamsgruber, Jörg; Portilla Berlanga, Luis; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2015)
The facile assembly of shell-by-shell (SbS)-coated nanoparticles [TiO2 -PAC16 ]@shell 1-7 (PAC16 = hexadecylphosphonic acid), which are soluble in water and can be isolated as stable solids, is reported. In these functional architectures, an umpolung of dispersibility (organic apolar versus water) was accomplished by the noncovalent binding of ligands 1-7 to titania nanoparticles [TiO2 -PAC16 ] containing a first covalent coating with PAC16. Ligands 1-7 are amphiphilic and form the outer second shell of [TiO2 -PAC16 ]@shell 1-7. The tailor-designed dendritic building blocks 3-5 contain negative and positive charges in the same molecule, and ligands 6 and 7 contain a perylenetetracarboxylic acid dimide (PDI) core (6/7) as a photoactive reporter component. In the redox and photoactive system [TiO2 -PAC16 ]@shell 7, electronic communication between the inorganic core to the PDI ligands was observed.